Factors determining conversion of laparoscopic to open cholecystectomy - Maitra, Tapash Kumar; Ekramullah, Mahmud; Faruquzzaman, -; Mondol, Samiran Kumar (IMC Journal of Medical Science, 2017)
Background and objectives: Laparoscopic cholecystectomy (LC) has virtually replaced conventional open cholecystectomy (OC) as the standard procedure of treatment for cholelithiasis and cholecystitis. However, OC sometimes becomes a necessity considering the feasibility and safety of the surgical procedure. But the factors that demand conversion from LC to OC differ widely. The present study aimed to determine the prevalence of conversion from LC to OC and to assess the causes of conversion and risk factors related to conversion. Methods: The study was conducted in a referral hospital Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorder (BIRDEM) from September 2014 to September 2016. Cases of cholelithiasis with or without cholecystitis, and other gall bladder pathology were included in the study. A team of experienced surgeon performed LC of all selected cases. The causes of conversion to OC were systematically recorded by the surgical team and the risk factors (age, sex, obesity, history of previous abdominal surgery, gallbladder thickness) related to conversion from LC to OC was investigated. Results: A total of 261 (M / F = 87 /174) patients were considered eligible for the study. The mean age of all patients was 43 (±1.75) years. For the male and female groups the mean ages were 44±1.9 and 42±1.6 years respectively. Of the total 261 cases, 210 (80.5%) patients had cholelithiasis with chronic cholecystitis, 47 (18.0%) had gallbladder stone plus acute cholecystitis and 4 (1.5%) had gallbladder polyp. Open conversion was required in case of 19 patients. Thus, overall conversion rate was 7.3%. The common causes of conversion were a) difficulty in defining Calots triangle (42.1%), b) injury to cystic artery (21.1%) and c) injury to bile duct (15.8%). Both male and female had equal risk for conversion. The investigated risk factors like history of previous abdominal surgery, preoperative ERCP, acute cholecystitis, obesity, increased gallbladder-wall thickness and older age showed no significant association with conversion. Conclusion: The study revealed that a very few patents (7.5%) needed conversion from LC to OC. The commonest cause of conversion was difficulty in defining Calots triangle, injury to cystic artery and bile duct. The risk factors like previous abdominal surgery, preoperative ERCP, gallbladder wall thickness, obesity and old age were not found associated with conversion to OC. IMC J Med Sci 2017; 11(2): 32-35